Screening for autologous blood transfusions - Mørkeberg, J.; Belhage, B.; Ashenden, M.; Bornø, A.; Sharpe, K.; Dziegiel, M. H.; Damsgaard, R. (International Journal of Sports Medicine, 2009)
The ratio between the amount of hemoglobin in the mature erythrocyte population and the reticulocytes (RBCHb:RetHb ratio) has previously been suggested as a marker to screen for EPO-abuse. We speculated that the reinfusion of blood would lead to a marked increase in this ratio, making it a valuable parameter in the screening for autologous blood doping. Three bags of blood (~201±11 g of Hb) were withdrawn from 16 males and stored at either -80°C (-80 T, n=8) or +4°C (+4 T, n=8) and reinfused 10 weeks or 4 weeks later, respectively. Seven subjects served as controls. Different erythrocyte parameters were measured on a hematological analyzer serially throughout and during a 4 week wash-out period. By using RBCHb:RetHb ratio cut-off limits of 145.7 (1:100) (`suspicious') and 182.9 (1:1 000) (`positive'), 35.4% (-80 T) and 19.6% (+4 T) of all samples obtained during a 4 week wash-out period were identified as `suspicious', and 18.8% (-80 T) and 4.3% (+4 T) as `positive'. In total, 7 out of 16 (43.8%) subjects had at least one sample exceeding 182.9. Compared to the currently used indirect parameters, the RBCHb:RetHb ratio is the best indicator of autologous blood doping after reinfusion, and the parameter could be used in a testing setting, once stability validation has been performed.